ANALISIS PENGGUNAAN ASET DALAM MENGUKUR PROFITABILITAS PT PERUSAHAAN GAS NEGARA (PERSERO) TBK MEDAN - Rizanul Akbar Assofi; Syafrida Hani (KITABAH: Jurnal Akuntansi dan Keuangan Syariah, 2017)
This study aims to analyze and observe the linkage of asset use and profitability of PT. Perusahaan Gas Negara (Persero) Tbk Medan abbreviated as PGN. The research was done by descriptive analysis approach. From 2011 to 2013 data, it was found that in addition to the turn over inventory ratio, the downward trend occurred in account receivable turnover ratio, fixed asset turnover, total asset turn over, and cash turnover, resulting in less stable profitability of firms, Continue to decline. Although the ratio of GPM, operating margin and NPM increased in 2012, but in 2013 all profitability ratios decreased. The decrease in activity ratios is likely to be due to an increase in company assets such as accounts receivable, fixed assets, total assets and substantial corporate cash each year, but is not accompanied by maximum revenues annually, although the company can keep its earnings stability increasing every year